The China Seismological Reference Model project - LianXing Wen; Sheng Yu (Earth and Planetary Physics, 2023)
The importance of developing high-resolution seismic models to improve understanding of tectonic processes and enhance seismic hazard mitigation programs, along with the rapid expansion of seismic coverage in China, called for a seismological reference model to be established in China. The China Seismological Reference Model (CSRM) project was initiated by the National Natural Science Foundation of China with two primary goals: (1) the CSRM would serve as a primary source for the current state of seismological research in China, and (2) the seismic data and constraints used to construct the CSRM would be used as a backbone open-access cyberinfrastructure for future research in seismology. The CSRM project was also intended to promote data exchange and scientific collaboration in seismology in China. Accordingly, two parallel efforts of the project are being pursued: (1) construction of the CSRM, and (2) development of a CSRM product center. The CSRM is jointly constrained by various types of seismic constraints extracted from the seismic data recorded at 4511 seismic stations in continental China following a top-down approach, with the seismic structures in the shallower part of the Earth constrained first. Construction of the CSRM involves three preparation steps: (1) building datasets of various seismic constraints from the seismic data, (2) developing a method to incorporate the constraints of surface wave observations from regional earthquakes into the inversion of the seismic structure, and (3) constructing high-resolution pre-CSRM seismic models of the velocity structure in the shallow crust and the Pn-velocity structure in the uppermost mantle. In the final process, the CSRM will be constructed by jointly inverting all the seismic constraints using the pre-CSRM models as starting models or a priori structures. The CSRM product center (http://chinageorefmodel.org) archives and distributes three types of products: CSRM models, the Level 1 original seismic data used to extract seismic constraints in the construction of the CSRM, and Level 2 data on the seismic constraints derived from the Level 1 data and the inferred earthquake parameters in the construction of the CSRM. The CSRM product center has archived 141 TB of Level 1 data from 1120 permanent broadband stations in the China Seismic Network Center and 3391 temporary stations from various institutions and data centers around the world, as well as 140 GB of Level 2 data on various seismic constraints and inferred event parameters from the construction of the CSRM. The CSRM is expected to provide significant insights into the composition and tectonic dynamics in continental China and to enhance the capability of various seismic hazard mitigation programs in China from near real-time rapid determination of earthquake parameters to an earthquake early warning system. The CSRM could also provide guidance for focuses in future seismological research and the design of future active and passive seismic experiments in China. Several focuses are suggested for future seismological research in China, along with the building of a national cyberinfrastructure to sustain and expand the operations of the CSRM project.